(untitled) (Clinics, 2020)
OBJECTIVES: Menopause marks the end of women’s reproductive period and can lead to sarcopenia and osteoporosis (OP), increasing the risk of falls and fractures. The aim of this study is to evaluate the influence of normal and low bone mineral density (BMD) on muscular activity, observed through inflammatory edema when mapping using magnetic resonance imaging (MRI) on the quadriceps muscle of postmenopausal women. METHODS: This was a cross-sectional study involving 16 older women, who were divided into two groups: osteoporosis group (OG), older women with OP, and control group (CG), older women without OP. The groups were evaluated in terms of nuclear MRI exam before and after carrying out fatigue protocol exercises using an isokinetic dynamometer and squatting exercises. RESULTS: The results of the present study showed that in intragroup comparisons, for both groups, there was a significant increase (po0.05) in the T2 signal of the nuclear MRI in the quadriceps muscle after carrying out exercises using both thighs. In the intergroup comparison, no statistically significant difference was observed between the OG and CG, pre- (p=0.343) and postexercise (p=0.874). CONCLUSION: The acute muscular activation of the quadriceps evaluated by T2 mapping on nuclear MRI equipment is equal in women with and without OP in the postmenopausal phase. BMD did not interfere with muscle response to exercise when muscle fatigue was reached.